Use of Plant Growth-Promoting Rhizobacteria in Maize and Sugarcane: Characteristics and Applications - dos Santos, Roberta Mendes [UNESP] (2020)
Free-living bacteria that actively colonize plant roots and provide positive effects on plant development are called plant-growth promoting. Plant growth-promoting bacteria can promote plant growth and use their own metabolism to solubilize phosphates, produce hormones and fix nitrogen, and they can directly affect plant metabolism. PGPR also increase plant absorption of water and nutrients, improving root development and increasing plant enzymatic activity; moreover, PGPR can promote other microorganisms as part of a synergistic effect to improve their effects on plants, promoting plant growth or suppressing pathogens. Many studies have shown several benefits of the use of PGPR in maize and sugarcane crops. These bacteria are an excellent alternative to farmers to reduce chemical fertilization and pesticide input without promoting the environment impact and yield-reducing. The present review is an effort to elucidate the concept of rhizobacteria in the current scenario and their underlying mechanisms of plant growth promotion with recent updates. The latest paradigms of a wide range of applications of these beneficial rhizobacteria in both crops maize and sugarcane have been presented explicitly to garner broad perspectives regarding their functioning and applicability. The results from several studies have shown that the utilization of PGPR in maize and sugarcane is the great alternative to farmers face the challenge the modern agriculture.